(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Gautum S, Koju NP. 2022. Demographic and health status of captive elephants around Chitwan National Park, Nepal. Biodiversitas 23: 1621-1627. Elephants have been captive from ancient times. As a keystone species, it requires proper care and management to sustain its viable population in the wild as well as a captive. However, there is a lack of study on captive elephants in Nepal. This study aimed to explore the status of captive elephants in Sauraha, Chitwan National Park, the top tourist destination of Nepal. Field survey, Key-Informant Interview (KII), and questionnaire survey were carried out for the primary source of data collection. During which, 78 mahouts were interviewed. The study revealed 97 (16 males and 81 females) captive elephants in Sauraha during the study period. Among them, 17 were born by captive mothers. The distance traveled by an elephant has recorded 16 km for minimum and 84 km in maximum per day and carries the average weight of 450 kg. Captive elephants belonging to the private company (N=60) were used only in tourism, while captive elephants from National Trust for Nature Conservation (NTNC) and Governments were used in patrolling and transportation. The most common disease in captive elephants is tuberculosis (27%). Similarly, parasitic infections, diseases like foot problems, and colic were also recorded. An effective policy and plan are urgently required to conserve this endangered umbrella species in captivity.